Kompetensi Kesantunan Berbahasa Sukarelawan Berpandukan Maksim Kesantunan Leech - Khazri Osman; Mohamad Yazid Abdul Majid; Mohamad Azrien Mohamed Adnan; Siti Salwa Jefri (PIMM Experts SDN BHD, 2024)
Volume: 8 No: 2 (page: 112-126)